Um olhar sobre a paternidade adolescente: especificidades de uma vivência - Prado, Marina de Moraes e (2011)
Adolescence could be considered as a transitional process which concerns intensive social, psychic and body experiences enabling resignifications about the establishment of identity process. In this context, fatherhood demands some psychic and social changes. This dissertation has as an objective to identify and address the perceptions and experiences of teenager parenthood from psychoanalytical theories. Two sections were written about this topic: a theoretical and an empirical one. From a literature review, the theoretical section refers to the psychoanalytical theories which enable a deep understanding concerning the experiences and conflicts of adolescence. The empirical section develops a qualitative study which intends to identify how male teenagers see and live their fatherhood experience identifying expectances and fears about becoming a father. Five male teenagers were interviewed between 12 and 18 years old whose parteners where in the third semester of pregnancy. Through the Analysis of Content, four final categories were identified and they are in the empirical section with participants‟ speech about it. The final categories are: Expectance and feelings about pregnancy and son: narcissist matters; Fatherhood presence in the pregnancy process: construction of potential; Fatherhood experience: resignification of life history and Specificities in the way of becoming a father in adolescence. The aspects found in this dissertation enabled us to get a better knowledge concerning the link between adolescence identity demands and experiences of fatherhood in this life stage. The participants of the study expressed to want to get a bond with their child and also this could serve as a way of resignification of their own childhood experiences with their parents. This study also reassures the importance of public and private politics which adds some important aspects to psychic health that belongs to the adolescence fatherhood experience. It was found as well that facing a teenager pregnancy it is necessary not restrict the understanding of the situation to some possible failures in the process of communication with adolescents concerning contraceptive methods but it is necessary to try to understand this situation as way to promote health of these teenagers involved in this kind of situation in which they have a new role which is being a father. Once again, it is important that these teenagers could be sheltered into a place that promotes conditions of elaboration of the conflicts and potential which each situation of fatherhood in adolescence from their specificities.